Pengembangan Instrumen Penilaian Pemahaman IPA Untuk Siswa Kelas IV Sekolah Dasar - Irhas, Irhas; Amikratunnisyah, Amikratunnisyah (Varied Knowledge Journal, 2023)
This study aims to design a science comprehension assessment instrument for grade IV force and motion material in terms of validity, reliability, difficulty level test, and differentiation of questions, and effectiveness test for multiple choice questions. This research is a development research of Borg & Gall's RDR (Research Development Research) model. The subject of this research assessment is a science comprehension assessment instrument. The data collection method of this research uses an objective test method. The test instrument used is a multiple choice objective test and true false to assess students' understanding of science. The content validity data analysis method uses the content validity coefficient -Aiken's V. The results of this study are the content validity test obtained a score of more than or equal to 0.5 including the high category, the item validity test produced 13 valid test items, the test reliability test of 0.501 including high criteria, the analysis of the differential power of the questions did not obtain questions with very good criteria, 3 good questions, 6 questions were quite good, and 4 questions were bad or not good, the analysis of the level of difficulty obtained the results that there were 9 questions with easy criteria, Based on the results of this study, the science understanding assessment instrument (C2) in the form of multiple choice and true-false test instruments that have been developed is declared to meet the criteria for good instrument quality.